2014
DOI: 10.7150/jca.8594
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1, XRCC1 and GSTP1 Single Nucleotide Polymorphisms and Survival of Patients with Colon Cancer Receiving Oxaliplatin-Based Adjuvant Chemotherapy

Abstract: Background: While single nucleotide polymorphisms (SNP) in genes involved in DNA repair or drug metabolism have been shown to influence survival of metastatic colon cancer patients treated with FOLFOX, data on adjuvant setting are scarce.Methods: This study evaluated the correlation between disease-free survival (DFS) of 210 unselected stage III colon cancer patients receiving FOLFOX chemotherapy, and ERCC1-118 (rs11615, c.354T>C), XRCC1-399 (rs25487, c.1196G>A) and GSTP1-105 (rs1695, c.313A>G) polymorphisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…In accordance with the current study, one CRC study reported a higher incidence of the C/T genotype, with 44% as compared to C/C (24%) and T/T (32%). [12] However, another reported that the frequencies of C/C, C/T, and T/T genotypes were 47.6%, 39.9% and 12.5%, respectively in Asian patients, very similar to previous reports in Caucasian populations. [4,13] In the present study, it was found that there was positive ERCC1 protein expression in 72% of CRC patients.…”
Section: Discussionsupporting
confidence: 78%
“…In accordance with the current study, one CRC study reported a higher incidence of the C/T genotype, with 44% as compared to C/C (24%) and T/T (32%). [12] However, another reported that the frequencies of C/C, C/T, and T/T genotypes were 47.6%, 39.9% and 12.5%, respectively in Asian patients, very similar to previous reports in Caucasian populations. [4,13] In the present study, it was found that there was positive ERCC1 protein expression in 72% of CRC patients.…”
Section: Discussionsupporting
confidence: 78%
“…Similar reports can be found in a meta-analysis conducted by Gu et al [10], who showed the correlation between XRCC1 Arg399Gln polymorphism and efficacy of platinum drug in treating NonSmall Cell Lung Cancer (NSCLC). Similar observations have been found in the treatment of colon cancer [14,22] and ovarian carcinoma [23] using platinum drugs. Kim et al also found the correlation between polymorphism of Arg399Gln and GSTP1 Ile105Val locus with treatment efficacy of platinum on colorectal carcinoma [24].…”
Section: Discussionsupporting
confidence: 71%
“…Repair function related with platinum drug resistance is mainly consisted of nucleotide incision and base removal/repairmen [7][8][9]. Current findings revealed that the repair potency of human X-ray Repair CrossComplementing gene 1 (XRCC1) was correlated with Single Nucleotide Polymorphism (SNP) at 399 th locus, thus affecting chemotherapy efficiency of platinum based drugs [10][11][12][13][14]. Xeroderma pigmentosum group D (XPD) gene facilitates DNA repair by denaturing damaged site.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that glutathione S-transferase P1 (GSTP1) and X-ray repair cross-complementing group 1 (XRCC1) genetic variations may influence the efficacy of chemotherapy in various cancers, such as colon cancer, gastric cancer, and ovarian cancer (Khrunin et al, 2010;Ji et al, 2013;Lai et al, 2013;Zaanan et al, 2014). Currently, many studies reported the role of GSTP1 and XRCC1 genetic polymorphisms in the clinical outcome of NSCLC, but the results are inconclusive.…”
Section: Introductionmentioning
confidence: 99%